Psoríase e obesidade: associação mútua? - Nadia Couto Bavoso (2014)
INTRODUCTION: Psoriasis is a highly prevalent dermatological disease. Although it is genetically based, it is substantially influenced by environmental factors. It is believed to be somewhat related to a low grade systemic inflammatory response. Cutaneous lesions show high levels of inflammatory citokynes as well. The prevalence of obesity has been shown to be elevated in patients with psoriasis and there are data showing that inflammatory citokynes are involved in the process. OBJECTIVES: To determine leptin and adiponectin levels in psoriasis patients as compared with those in control patients. To determine the prevalence of obesity and overweighth in patients with psoriasis. To evaluate if high levels of leptin and low levels of adiponectin are related to psoriasis independently of the concomitance of obesity. To assess if the levels of leptin and adiponectin and the obesity grade are related to psoriasis severity. METHODS: A case control study was performed, and 113 psoriasis patients and 41 controls with other dermatologic diseases were evaluated between April 2012 and November 2012. The subjects were evaluated for severity of psoriasis and anthropometric measures were taken. All patients involved answered life quality questionnaires and filled out a form with the clinical history. Blood samples for dosage of citokyines were collected. For the univariated analyses we used the x² test and the Mann-Whitney test. For the multivariated analysis, we used the binary logistic regression model. After the final model adjustmens, the (OR) logistic (IC95%) was calculated. All the analyses were stratified between cases and controls. RESULTS: In this sample, the mean age was 55.3 years in cases and 39.9 years in controls. Among cases we found 56.6% females and 43.4% males. In the control group, 46.3% were females and 53.7% were males. The prevalence of obesity was 33% in cases and 21.9% in controls. The prevalences of all the comorbities evaluated were higher in cases. When stratified by weight, the comorbidities were more frequent in overweight patients. We have not found any correlation between been overweight (p=0.25) and leptin (p= 0.18) and adiponectin (p= 0.762) levels and psoriasis severity. When overweight cases and controls were compared, we found differences in the adiponectin values (p= 0.04). The overweight cases had lower adiponectin levels when compared to overweight controls. We could not observe differences in the leptin dosage of cases and controls. The overweight cases had higher leptin values than the normal weight cases (p<0.001). CONCLUSIONS: The prevalence of obesity among psoriasis cases (33%) was higher than in the general population (17.4%). We did not find any correlation between severity of psoriasis and inflammatory citokynes and the fact of being overweight. The overweight cases had lower values of adiponectin than the overweight controls. It seems, therefore, that there is a relationship between adiponectin and psoriasis, but this relationship depends on the presence of obesity.